ARM AND LEG IDIOMS IN THE BNC AND COCA CORPORA: VIEWS ON THE CULTURAL DIFFERENCES BETWEEN BRITISH AND AMERICAN SOCIETY - Nevena Tanasić (International Journal of Cognitive Research in Science, Engineering and Education, 2014)
Phraseological units, primarily idioms are those types of linguistic units which reveal to a great extent how certain linguistic community copes with its surroundings. The aim of the paper is to demonstrate how idioms in English language are actually differently used across different genres in British and American linguistic communities, and try to explain those results in light of the Sapir-Whorf Hypothesis. The study was conducted on the basis of the idioms that have the same body part, namely arm and/or leg, and those idioms were then compared in two corpora – the BNC (British National Corpus) and COCA (Corpus of Contemporary American English).